Analisis Desain Dan Ragam Bahasa "Beda Pemula Bikin Konten vs. Udah 1 Tahun Oleh Victoriawong" - Sonya Hutabarat; Miranda Elisa Br Sembiring; Sonya Apriyanti Damanik; Renita Br Saragih (Concept: Journal of Social Humanities and Education, 2023)
The purpose of this qualitative research is to determine the types of language variety in the Tiktok content "Different Beginners Making Content Vs. Already 1 Year by Victoriawong" and to analyze the content design. After downloading videos from tiktok Victoriawong, data collection techniques are used to listen, record, identify, and classify. The purpose of this study is to analyze the design and describe the variety of languages used by content creators. Based on the results of an analysis of the variety of languages in Beda content, Beginners create Content Vs. It's been 1 year by Victoriawong, the most widely used is colloquial language with a percentage of 37% of the 10 words that contain colloquial language. The second highest percentage is journalistic variety 14.8%, spoken variety 14.8%, casual language, 14.8% of each of the 4 words that the researcher gets. The least presentation, namely the variety of formalities, is 11.1% of the 3 words. And the variety of languages that are not included in this content are the variety of dialects and the variety of businesses.